An Analysis of the Role of Management in Nuclear Disasters using Text Mining - Novak, J.; Brunetto, Y.; Brown, Kerry (Atlantis Press, 2014)
This study uses text mining as a method of examining the role of management and culture in three disasters in the nuclear energy sector, Three Mile Island nuclear reactor explosion (USA 1979), Chernobyl nuclear plant explosion (Ukraine then USSR 1986) and the Fukushima Daiichi nuclear disaster (Japan 2011). The findings identify the role of management in shaping the quality of the crisis and disaster mitigation and preparedness management process employed by organisations. The implications of the findings are that it is imperative for organisations to develop and employ effective crisis/disaster management practice.